TYPOLOGY OF POLITICAL PARTICIPATION FORMS - I. I. Gandaloev (Современная наука и инновации, 2022)
In the article, the author, having analyzed a wide range of relevant scientific literature, identifies three approaches to the definition of political participation: «optimistic», «pes-simistic» and «realistic». Proving the prevalence of the «realistic» approach in modern research, he comes to the conclusion that scientists are analyzing a wide variety offorms ofpolitical participation, which requires systematization. As a result, he offers the author's typology of political participation forms, which includes seven criteria.